Oral health status of patients over 18 years. Preventive clinic practicum I, Unne School of Dentistry, Argentina, 2010 - Dhó, María S.; Vila, Vilma G.; Palladino, Alberto C. (Revista Facultad de Odontología Universidad de Antioquia, 2013)
Introduction: with the intention of identifying the oral health status of patients attending the Preventive Clinic Practicum i at the School of Dentistry, Universidad nacional del nordeste (Unne), argentina, a cross-sectional study was conducted between September and october 2010. Methods: the variables taken into account were: socio-demographic data, level of oral health knowledge, oral hygiene habits and carbohydrate consumption, gingival status, oral hygiene, teeth status, and access to dental care. the data were collected by means of structured self-administered surveys and the medical records of each patient, and they were analyzed with the statistical software SPSS® 15.0 and epidat® 3.1. Results: although a good level of oral health knowledge is predominant, it is not reflected in oral hygiene habits or in the frequency in which individuals seek preventive dental care. the clinical examination revealed poor oral hygiene habits, high prevalence of mild gingivitis and high prevalence of dental caries as well as filled and missing teeth as a result of it. Conclusions: it is necessary to search for strategies to optimize health education and to improve preventive behaviors within the study population.